2009
DOI: 10.1002/ibd.20916
|View full text |Cite
|
Sign up to set email alerts
|

Increased number and activation of colonic macrophages in pediatric patients with untreated Crohnʼs disease

Abstract: Histologically normal colon mucosa contains fewer macrophages in children than in adults. However, in colon of children with untreated CD the mucosal macrophage density is increased. Activated mucosal macrophages are increased in untreated pediatric IBD regardless of inflammatory grade. Such upregulated innate mucosal immune activation may contribute to the colonic phenotype of childhood CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 262 publications
(387 reference statements)
1
15
0
Order By: Relevance
“…In contrast, the count of CD40+ in the colon of CD children was markedly elevated, compared to the controls. Moreover, the CD children showed a tendency for a higher density of CD40+ cells in the colon, compared to UC patients (mean rank 10.7 vs. 8.7) [28].…”
Section: Discussionmentioning
confidence: 89%
“…In contrast, the count of CD40+ in the colon of CD children was markedly elevated, compared to the controls. Moreover, the CD children showed a tendency for a higher density of CD40+ cells in the colon, compared to UC patients (mean rank 10.7 vs. 8.7) [28].…”
Section: Discussionmentioning
confidence: 89%
“…A rapid early progression was reported in CD, with about one third of patients demonstrating complicated disease at diagnosis, including proximal disease [11], and with about two thirds showing complicated disease at the seventh year of follow-up [11]. A different immunologic expression during childhood, on the basis of a genetically transformed innate immune system, may explain the different clinical phenotypes among adults and children with IBD [47]. An interesting shift from male to female predominance around the age of puberty is unclear.…”
Section: Pediatric Problemsmentioning
confidence: 94%
“…Indeed, causes underlying this disease are likely multifactorial. In general, studies have shown an increase in both DC and macrophage populations in the intestinal lamina propria in Crohn's Disease patients [20,32,33,[50][51][52]. Studies have also consistently shown that DCs in Crohn's Disease are more activated and have higher expression of microbial recognition receptors, particularly TLR4 [8,27,50,53,54].…”
Section: Phagocyte Subsets In the Intestine Of Patients With Crohn's mentioning
confidence: 98%